Am Impact of TV Advertising on Brand Switching of Facial Skin Care Products toward Thai Women - Chaisavetkanon, Patchara (2009)
It is widely accepted that “women” and “beauty” can hardly set apart. Women desire for a young looking skin and healthy, especially from inside-out. Colour cosmetics are believed to make them look more beautiful, charming, and have better personality. However, many people including dermatologists, make-up artists, women themselves, or even men do agree that having a healthy skin is the true secret behind women’s beauty. People tend to be more loyal to skin care brands than other toiletries because they believe that the skin care products would treat directly onto their skin. These reasons encourage skin care companies to compete to be leading and trusted brands in the minds of consumers. They invest in new product development and plan efficient marketing strategies, including advertising campaigns in order to grab their target market’s attention, convince them to try and buy the products, retain their loyalty, and switch to their brands eventually. This dissertation studies about an impact of TV advertising (the medium with the highest investment by many skin care firms in Thailand) on brand switching of facial skin care products toward Thai women particularly. The literature review provides theories about advertising and its effects on brand switching, consumers’ perceptions/behaviours and so on. The qualitative research conducted with ten Thai women is employed to gain as much useful insights and understanding as possible in order to come up with the research findings, analysis and conclusions to the research question. The results show that TV adverts could create brand awareness, provide brief product information, entertain audiences, and to some extent recalling them the brands usually advertised. However, the consumers especially those who are well-educated do not easily believe and get convinced by the TVCs, rather searching for more useful information such as word-of-mouth. Yet, it is still believed that TV adverts are the powerful media tool in communicating between the companies and the mass consumers. In addition, the interview with Thai women living in different countries (UK and Thailand) emphasises that the very important factors for consumers’ choices of medium and brand selection are the level of education, backgrounds and life styles, rather than the places where they are living.